Non-violence as a Shifting Signifier on the Tibetan Plateau. Issue 1 (2nd January 2016) - Gayley, Holly; , Padma 'tsho
Abstract: In nomadic areas, Tibetans are wearing a new amulet, called an 'amulet for peace', depicting a globe with a dove flying above it. The dove carries a bodhi leaf in its mouth and a gold peace sign in its claws, combining Buddhist and global symbols for peace. However, the amulet is not being marshalled for Gandhian-style non-violent resistance nor world peace for that matter, but rather for something more local. This local cause is a campaign to end fighting over the grasslands, a sustained social problem in nomadic areas of eastern Tibet. The amulet for peace is a recent innovation, launched in 2012 as part of an ethical reform movement spearheaded by Larung Buddhist Academy, the largest monastic institution on the Tibetan plateau. This article discusses the latest developments in this emerging movement and, specifically, the significance of the amulet for peace and the discourses in which it is embedded.